Afroaid Magyarország Egyesület - Csefkó, Tamás (Afrika Tanulmányok / Hungarian Journal of African Studies, 2008)
Afroaid Hungary Association is a public utility that launches mutual aid programmes in co-operation with local volunteers in various African countries. Their activity is of humanist and not of humanitarian nature. They do not provide material support. Instead, they share their experience in developing organizations and community building with the inhabitants of the given settlement. Through this initiative local people can make changes both in their communities and in their personal lives. The projects of Afroaid Hungary are based on the principle of reciprocity: everyone whose living conditions improve due to community activities should contribute to making the life of the community better. The association wants to help people restore their belief in themselves, leave despondency, passivity and indifference and direct their own destiny. It is mainly active in the fields of public health, public education, the quality of life and active non-violence.